Visi bantuan IMF dan problematik beban ekonomi nasional - Edy Suandi Hamid (Economic Journal of Emerging Markets, 1997)
When Indonesian government asked IMF to help setting Indonesia out of the currency exchange crisis lately, there are contra as well as pro among Indonesian economist. The ones who contradicted the policy argued that, as it was known. IMF's assistance is a conditional assistance.